Heart rate responses during biathlon races of different lengths in elite athletes - Zinner, C.; Willis, S.; Jonson, M.; Sperlich, B.; Holmberg, H. C. (Science and Skiing VI. 6th International Congress on Science and Skiing, Dec. 14 - 19, 2013, St. Christoph am Arlberg, 2015)
The aims of the study were threefold: 1) to describe heart rate profiles (of elite athletes) during biathlon World Cup races of different events and distances; 2) to estimate exercise intensity during the competitions using heart rate; and 3) to compare differences in heart rate between men and women. Volltext unter: https://www.researchgate.net/publication/270898281_Heart_rate_responses_during_biathlon_races_of_different_lengths_in_elite_athletes